Simultaneous Determination of Five Alkaloids by HPLC-MS/MS Combined With Micro-SPE in Rat Plasma and Its Application to Pharmacokinetics After Oral Administration of Lotus Leaf Extract - Zou, Shuhan; Ge, Yuanyuan; Chen, Xuanhao; Li, Jin; Yang, Xuejing; Wang, Hui; Gao, Xiumei; Chang, Yan-xu (Frontiers in Pharmacology, 2019)
An environment-friendly and effecient method for simultaneous determination of five alkaloids (nunciferine, O-nornuciferin, liriodenine, armepavine and pronuciferine) in rat plasma was established by HPLC-MS/MS associated with micro solid phase extraction (micro-SPE). The plasma sample was pretreated by using micro-SPE columns filled with polymer materials PEP-2 and eluted by little organic solvent (400 µL acetonitrile). The five alkaloids were separated with acetonitrile and 0.1% formic acid aqueous solution on Eclipse plus C18 column. The mode of positive electrospray ionization was used to measure the analytes in multiple-reaction monitoring (MRM). The determination coefficients (R2) of the five alkaloids were greater than 0.99. The lower limit of quantification (LLOQ) of O-nornuciferin, liriodenine and armepavine was 0.5 ng·mL-1, that of nunciferine and pronuciferine was 1 ng·mL-1. The validated method was effectively used for the pharmacokinetics of orally administrated the five alkaloids of lotus leaf extract in rat plasma.